Unions and collective bargaining in Australia in 2016. (June 2017) - Nicholson, Daniel; Pekarek, Andreas; Gahan, Peter
In 2016, Australian unions faced a mix of new and enduring challenges. A re-elected Conservative federal government made life difficult for unions, maintaining its hard-line approach to public sector bargaining and passing new laws to intensify regulatory scrutiny of union governance and tactics. Unions continued to secure wage premiums through enterprise bargaining, but the longer-term decline in the level of agreement-making and the number of workers covered by enterprise agreements continued. Disputation rose, although less than half of all disputes were caused by enterprise bargaining. Concern over ongoing membership decline saw unions explore and experiment with organisational reforms and initiatives as new, 'union-like' actors entered the field. However, our analysis of longer-term membership developments across union types suggests the outlook is alarming for all but those unions focused on occupational identity.